Serological investigation of plague and brucellosis infection in Marmota himalayana plague foci in the Altun Mountains on the Qinghai-Tibet Plateau - Qin, Shuai; Liang, Junrong; Tang, Deming; Chen, Yuhuang; Duan, Ran; Lu, Xinmin; Bukai, Asaiti; Zheng, Xiaojin; Lv, Dongyue; He, Zhaokai; Wu, Weiwei; Han, Haonan; et al. (Frontiers in Public Health, 2022)
The Altun Mountains are among the most active regions of Marmota himalayana plague foci of the Qinghai-Tibet Plateau where animal plague is prevalent, whereas only three human cases have been found since 1960. Animal husbandry is the main income for the local economy; brucellosis appears sometimes in animals and less often in humans. In this study, a retrospective investigation of plague and brucellosis seroprevalence among humans and animals was conducted to improve prevention and control measures for the two diseases. Animal and human sera were collected for routine surveillance from 2018 to 2021 and screened for plague and brucellosis. Yersinia pestis F1 antibody was preliminarily screened by the colloidal gold method at the monitoring site to identify previous infections with positive serology. Previous plague infection was found in 3.2% (14/432) of the studied human population having close contact with livestock, which indicates evidence of exposure to the Yersinia antigen (dead or live pathogenic materials) in the Altun Mountains. Seroprevalence of brucellosis was higher in camels (6.2%) and sheepdogs (1.8%) than in other livestock such as cattle and sheep, suggesting a possible transmission route from secondary host animals to humans.